DIMENSIONS ANALYSES OF CULTURE, CULTURE STYLE, BARRIER IN COMMUNICATING, DAN TYPE OF CORPORATE CULTURE FROM CERIA STORE - Dion Dewa Barata; Angela Angela; Caroline Marninda; Lian Andrianus; Titan Martinus; Sun Bhuan (Journal of Global Business and Management Review, 2023)
Ceria Shop is a minimarket located in Tanjungpinang and has been operating since 2012, of course it has a work culture that develops in the work environment itself which can affect performance, ways of interaction, communication between employees and superiors at work. In order to improve business development, work culture also plays an important role so that an analysis will be carried out on dimensions of culture, culture style, barriers in communicating, and types of corporate culture at Ceria Shop using qualitative methods and data collection by direct interviews with Ceria Shop owners. Based on the results of the analysis using Hofstede's theory, Globe Taxonomies, Trompenaar's, business culture, and several other theories, it can be seen that this minimarket has an Asian work culture with some adjustments to the environment or work situation. Employees still have freedom of opinion, strong bonds between peers and superiors, gain appreciation, and gender equality in conditions where superiors still give strict directions and focus on serving consumers. Overall Ceria Shop has been running well, but it would be better if superiors also pay attention to the work culture that each individual has when they want to work at Ceria Shop besides their work performance because the incompatibility of work culture can cause internal problems.